Journal publishing challenges: a case of STM scientific journals in Croatia - Vrana, Radovan (Array, 2012)
This paper presents findings from the research of 87 scientific journals in the fields of science, technology and medicine (STM) in Croatia. Findings indicate a set of problems editors and editorial teams in the fields of STM encounter during their work such, as insufficient financial support to the journal, low quality of article manuscripts, badly formatted article manuscripts, lack of help to the editor, etc. Findings also indicate use of information and communication technology (ICT) for communication with authors, but ICT is still not used sufficiently to make the shift from print to electronic publishing possible. Most journals in research face financial problems, and they are understaffed, while editors are overburdened with other duties. The recommendation is to professionalize the management of the journals to allow editors and their associates to dedicate their time solely to this job in order to facilitate the transformation of scientific journals from paper to electronic versions and to participate actively in the scientific communication paradigm shift.